Kinetic studies of ethylene oxidation by potassium permanganate adsorbed on rice hull ash, lahar ash or coconut coir dust - Hernandez, Alvin B.; Serrano, Edralina P.; Del Rosario, Ernesto J. (2007)
The ethylene scrubbing (oxidizing) efficiency and stability of KMnO 4 adsorbed on rice hull ash, lahar (volcanic ejecta) ash or cocqnut coir dust as carrier were evaluated. Values of the kinetic order with respect to ethylene of the reaction between C2H4 and KMnO 4 were 1.35 ± 0.39, 0.84 ± 0.18 and 1.46 ± 1.09 for rice hull ash, lahar ash and coconut coir dust, respectively. The permanganate-dependent and intrinsic (permanganate-independent) rate coefficients (k and k, respectively) were calculated based on pseudo-first order kinetics. The optimum KMnO4 concentration for scrubbing ethylene was found to be 0.04 M. Experimental values of the rate coefficient k' (in min -1) were 0.0216 ± 0.0020, 0.0127 ± 0.0003 and 0.0085 ± 0.0006 for rice hull ash, lahar ash and coconut coir dust, respectively. Values of the intrinsic rate coefficient k (in min-1 g carrier/g KMnO4) were 1.87,4.78 and 0.02 for rice hull ash, lahar ash and coconut coir dust, respectively. At the same KMnO4 loading, lahar ash was the most efficient KMnO4 carrier followed by rice hull ash and coconut coir dust. However, the most efficient KMnO4 carrier (per gram) as ethylene scrubber was rice hull ash followed by lahar ash and then coconut coir dust. Scrubber stability was determined by measuring how fast the rate coefficient k' and chromacity (intensity of KMnO4 color) changed with time. The rice-hull-ash-based scrubber was the most stable and showed negligible changes in rate coefficient k' for 27 d; lahar ash was the least stable carrier followed by coconut coir dust.
Keywords: Oxidation; Coconut coir; Rice hulls; Lahars